Pauli paramagnetism of cubic V3Al, CrVTiAl, and related 18-electron Heusler compounds with a group-13 element - Venkatesan, Munuswamy; Coey, John; Rode, Karsten (My University, 2021)
Calculations suggest that ordered Heusler alloys with 18 valance electrons could exhibit a variety of unusual electronic and magnetic states that are absent in the constituent elements. They include magnetic semiconductors, spin gapless semiconductors, compensated ferrimagnetic half-metals, and metallic antiferromagnets. Magnetic order has been predicted at exceptionally high temperature. Any of this would be of interest for spin electronics. Here, we investigate the magnetic properties of bulk, single-phase V3Al, CrVTiAl and the corresponding Ga compounds, with and without 57Fe doping. Results are compared with data on the constituent elements. We conclude that all the as-cast alloys show some degree of B2-type ordering, but all of them are Pauli paramagnets with dimensionless susceptibilities close to the average of the atomic constituents. Prolonged annealing of the single-phase as-cast alloys leads to phase segregation. Density functional theory calculations on V3X and CrVTiX with X=B, Al, Ga, and In confirm that different atomic arrangements on the four interpenetrating face-centered cubic sublattices of the Heusler structure could indeed lead to unusual magnetic properties, but both magnetism and semiconductivity are destroyed by disorder. The energy and entropy differences between different ordered magnetic phases preclude the stabilization of any single one of them. All are metastable and inaccessible in alloys prepared from the melt.
PUBLISHED
Keywords: Paramagnetism; Half-metals; Heusler alloy; Nanoscience & Materials; FABRICATION; NANOSTRUCTURES; Nanotechnology; Physics; SEMICONDUCTOR DEVICES AND MATERIALS; Theoretical Physics